Invasive pulmonary aspergillosisas a complication of severe influenza (case report) - Yu. E. Melekhina; O. V. Shadrivova; E. V. Frolova; Yu. V. Borzova; E. V. Shagdileeva; T. S. Bogomolova; O. A. Schurpitskaya; N. N. Klimko (Журнал инфектологии)
During  last  years  the  frequency  of  invasive  pulmonary aspergillosis  (IPA)  in  immunocompetent  patients  has  increased. Clinical case report of successful treatment invasive aspergillosis  with  influenza  A(H1N1)  presented  in  the  article. We analyzed the special literature of patients with IPA following influenza infection. The timely identification and treatment of these patients are necessary.